Right- versus left-sided congenital diaphragmatic hernia: postnatal outcome at a specialized tertiary care center - Schaible, Thomas; Kohl, Thomas; Reinshagen, Konrad; Brade, Joachim; Neff, Wolfgang; Stressig, Rüdiger; Büsing, Karen-Anett (Pediatric critical care medicine, 2012)
Objective: To systematically investigate the impact of the location of the defect in congenital diaphragmatic hernia on neonatal mortality and morbidity with a special focus on survival at discharge, extracorporeal membrane oxygenation requirement, and the development of chronic lung disease., Design: Retrospective tertiary care center study with a matched-pair analysis of all fetuses that were treated for congenital diaphragmatic hernia between 2004 and 2009., Setting: A specialized tertiary care center for fetuses with congenital diaphragmatic hernia., Patients: Complete sets of data were available for 106 patients with congenital diaphragmatic hernia. For 17 of 18 infants with right-sided congenital diaphragmatic hernia we were able to allocate infants with left-sided congenital diaphragmatic hernia with no relevant difference in previously described prognostic factors, such as pulmonary hypoplasia and liver herniation., Interventions: None., Measurements and Main Results: There was a strong trend toward better survival in infants with right-sided congenital diaphragmatic hernia than with left-sided congenital diaphragmatic hernia (94% vs. 70%; p = .07). More neonates with left-sided congenital diaphragmatic hernia died of severe pulmonary hypertension despite extracorporeal membrane oxygenation. Fewer neonates with right-sided congenital diaphragmatic hernia died, yet higher degrees of pulmonary hypoplasia and oxygen requirement were observed despite extracorporeal membrane oxygenation., Conclusions: In congenital diaphragmatic hernia, the location of the defect has a substantial impact on postnatal survival and the development of chronic lung disease. In left-sided congenital diaphragmatic hernia, pulmonary hypertension resistant to therapeutic management, including extracorporeal membrane oxygenation, is more common and is associated with a higher rate of neonatal demise. Right-sided congenital diaphragmatic hernia infants have an increased benefit from extracorporeal membrane oxygenation but the better survival entails a higher rate of chronic lung disease., (C)2012The Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies